2016
DOI: 10.2174/0929867323666160607111220
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Stim and Orai Proteins as an Alternative Approach in Anticancer Therapy

Abstract: An increase in intracellular Ca2+ concentration plays a key role in the establishment of many cancer hallmarks, including aberrant proliferation, migration, invasion, resistance to apoptosis and angiogenesis. The dysregulation of Ca2+ entry is one of the most subtle mechanisms by which cancer cells overwhelm their normal counterparts and gain the adaptive advantages that result in tumour growth, vascularisation and dissemination throughout the organism. Both constitutive and agonist-induced Ca2+ influx may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 0 publications
3
74
0
Order By: Relevance
“…In mammals there are three Orai genes that encode for Orai1, 2 and 3 proteins which function as pore forming subunits of CRAC channels in different cellular contexts [10,12,20,42,50]. The name Orai was given on the basis of Greek mythology (Orai are the keepers of heaven’s gate) after they were established as the long sought mediator of CRAC currents in immune cells [51].…”
Section: Dissecting the Molecular Mechanisms Of Store-operated Calmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals there are three Orai genes that encode for Orai1, 2 and 3 proteins which function as pore forming subunits of CRAC channels in different cellular contexts [10,12,20,42,50]. The name Orai was given on the basis of Greek mythology (Orai are the keepers of heaven’s gate) after they were established as the long sought mediator of CRAC currents in immune cells [51].…”
Section: Dissecting the Molecular Mechanisms Of Store-operated Calmentioning
confidence: 99%
“…Although originally identified as a mechanism for ensuring the refilling of intracellular stores following Ca 2+ release [15,16], SOCE is now directly linked to the activation of specific cellular functions, differently regulated depending on the stimulus and the cell type [10], including immune system activation [17], fluid secretion in salivary gland acinar cells [18], neurogenesis and neuronal excitability [12,19], cancer cell migration and metastasis [20], endothelial cell proliferation [21], skeletal muscle contractility [22], smooth muscle migration and proliferation [23,24], cardiac hypertrophy [25], cell cycle and cell proliferation [26], and gene expression [27]. Further, increasing evidences have recently identified the contribution of SOCE in thrombopoiesis, the process that ensures the differentiation of megakaryocytes, the platelet precursors, and final platelet production [28].…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that an increase in intracellular Ca 2+ concentration ([Ca 2+ ] i ) plays a key role in the complex and multistepped process of angiogenesis (Moccia, Berra‐Romani, & Tanzi, ; Moccia, Tanzi, & Munaron, ). This notion dates back to the earlier experiments conducted with carboxyamidotriazole, a non‐selective inhibitor of a plethora of Ca 2+ ‐permeable channels (Dragoni, Turin, et al, ; Moccia, Dragoni, et al, ; Moccia et al, ), that was shown to inhibit angiogenesis both in vitro and in vivo (Kohn, Alessandro, Spoonster, Wersto, & Liotta, ; Moccia et al, ; Patton, Kassis, Doong, & Kohn, ). An elevation in [Ca 2+ ] i represents a critical hub for the intricate network of signaling pathways evoked by extracellular growth factors (Moccia, ; Moccia, Berra‐Romani, & Tanzi, ; Moccia & Poletto, ; Moccia, Tanzi, & Munaron, ).…”
Section: Introductionmentioning
confidence: 96%
“…Upon ER store depletion, STIM1 aggregates and translocates to plasma membrane and then interacts directly with Orai1 and/or TRPC1 to form open SOCs that cause SOCE . Interestingly, the three constituents of SOCE, Stim1, Orai1 and TRPC1, have been detected in liver cells and associated with the initiation and progression of liver cancer . Previous work in HCC‐LM3 hepatoma cells showed that blockade of STIM‐mediated SOCE decreased the focal adhesion turnover and thus inhibited cell migration .…”
Section: Introductionmentioning
confidence: 99%